Pengaruh Latihan Smallside Games 2 Vs 2, 3 Vs 3, 4 Vs 4 Terhadap Kelincahan Menggiring Bola Sepak - Wea, Yovinianus Mbede (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2020)
ABSTRACTThis study aims to reveal the effect of the small side games 2 VS 2, 3 VS 3, 4 VS 4 exercise towards the agility on the football game at the eighth grade students of Mauponggo 1 state junior high school school year 2018/2019. The static group pretest posttest design was used in this study. This study was conducted in Thomas Aquino 1 state junior high school. The sample of this study consisted of 30 students and then they were categorized into two groups. They were the control group and the experiment group numbered in 15 students for each group. The data were collected using the action test. The data collected were analyzed using score gain normalized with ttest technique. Based on the result of the study through the hypothesis test shows that there is a significant effect on the experiment group or the given treatment group namely by the small side games (2 VS 2, 3 VS 3, 4 VS 4) exercise. Based on the count mean found that the experiment group is bigger than the control group(µ1= 0.0250 > µ1= 0.0196). Moreover, from the result of the t-test analysis got above is the value of tcount = 3.654 and ttable = 2.048 and ttable for dk: 15 + 15 – 2 = 28 at the significant standard α = 0,05 (the test of two tails) is 2.048. Because of the ttable = 2.048 is smaller than tcount = 7.970, so that H0 rejected and H1 accepted. In conclusion, the small side games (2 VS 2, 3 VS 3, 4 VS 4) exercise is influential towards the agility on the football game at the eighth grade students of SMAK Thomas Aquino1 state junior high school school year 2018/2019. ABSTRAKTujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui pengaruh latihan Small Side Games (2 VS 2, 3 VS 3, 4 VS 4) terhada kelincahan dalam permainan sepak bola siswa kelas VIII SMAK Thomas Aquino tahun ajaran 2018/2019. Penelitian ini menggunakan rancangan The Static-group pretes-posttest. Penelitian ini dilaksanakan  di SMAK Thomas Aquino dengan jumlah sampel sebanyak 30 orang yang kemudian dikategorikan kedalam 2 kelompok  yaitu 1 kelompok kontrol dan 1 lagi kelompok eksperimen dengan masing-masing berjumlah 15 orang. Data dikumpulkan dengan tes tindakan, kemudian data yang terkumpul dianalisis gain skor ternormalisasi dengan teknik t-tes. Berdasarkan hasil yang diperoleh melalui uji hipotesis, bahwa ada pengaruh yang sangat signifikan pada kelompok eksperimen atau kelompok yang diberi perlakuan (treatment), yaitu dengan latihan Small Side Games (2 VS 2, 3 VS 3, 4 VS 4). Berdasarkan rata-rata hitung ditemukan bahwa kelompok eksperimen lebih besar dari kelompok kontrol (µ1= 0.0250 > µ1= 0.0196). Selain itu, dari hasil analisis uji t di atas diperoleh nilai t-hitung sebesar 3.654 dan t - tabel untuk dk : 15 + 15 – 2 = 28 dengan taraf signikansi α = 0,05 (uji dua pihak) adalah 2.048. Karena t-tabel 2.048 lebih kecil dari t-hitung 7.970, maka H0 ditolak dan H1 diterima. Kesimpulanya bahwa latihan small side games (2 VS 2, 3VS 3, 4 VS 4) berpengaruh terhadap Kelincahan Sepak Bola siswa SMAK Thomas Aquino tahun ajaran 2018/2019